The relationship between gratitude and well-being: The moderating effect of religiosity on university freshmen during the COVID-19 pandemic - Daulay, Nurussakinah; Assingkily, Muhammad Shaleh; Munthe, Abdul Kholik (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
The various challenges and difficulties faced by college and university freshmen (new students) during the COVID-19 pandemic can affect their well-being. This well-being condition is influenced by gratitude and religiosity, as well as the role of religiosity in moderating these relations, are the main objectives of this study. The research was conducted on new students in the 2020/2021 and 2021/2022 academic years (N = 2048). Data collection was made through surveys by distributing online questionnaires, including the Gratitude Questionnaire-6, the Short Muslim Belief and Practice Scale, and the WEMWBS Scale. Data analysis was performed using multiple regression and a moderation test. The results show an influence of gratitude (β = .928, p < .01) and religiosity (β = .371 p < .01) on well-being. Religiosity is demonstrated to moderate the relationship between gratitude and well-being (F = 251.656, p < .01). The study has empirical implications in the form of the theory that career achievement and well-being orientation for new students will face various problems, but can be helped by introducing self-protective factors in the form of well-being, religiosity, and gratitude.